Limiting collagen turnover via collagenase‐resistance attenuates right ventricular dysfunction and fibrosis in pulmonary arterial hypertension. Issue 11 (1st June 2016) - Golob, Mark J.; Wang, Zhijie; Prostrollo, Anthony J.; Hacker, Timothy A.; Chesler, Naomi C.
Abstract: Pulmonary arterial hypertension (PAH) is a severe form of pulmonary hypertension in which right ventricular (RV) afterload is increased and death typically occurs due to decompensated RV hypertrophy and failure. Collagen accumulation has been implicated in pulmonary artery remodeling, but how it affects RV performance remains unclear. Here, we sought to identify the role of collagen turnover, defined as the balance between collagen synthesis and degradation, in RV structure and function in PAH. To do so, we exposed mutant (Col1a1 R/R ) mice, in which collagen type I degradation is impaired such that collagen turnover is reduced, and wild‐type (Col1a1 +/+ ) littermates to 14 days of chronic hypoxia combined with SUGEN treatment (HySu) to recapitulate characteristics of clinical PAH. RV structure and function were measured by echocardiography, RV catheterization, and histology. Despite comparable increases in RV systolic pressure (Col1a1 +/+ : 46 ± 2 mmHg; Col1a1 R/R : 47 ± 3 mmHg), the impaired collagen degradation in Col1a1 R/R mice resulted in no RV collagen accumulation, limited RV hypertrophy, and maintained right ventricular‐pulmonary vascular coupling with HySu exposure. The preservation of cardiac function in the mutant mice indicates a beneficial role of limited collagen turnover via impaired degradation in RV remodeling in response to chronic pressure overload. Our results suggest novel treatments that reduce collagen turnover may offer a new therapeutic strategy for PAH patients. Abstract : By the novel use of a mouse model of PAH with impaired collagen degradation, our study shows that the inhibition of collagen turnover attenuates RV collagen accumulation, limits RV hypertrophy, and preserves cardiac function. These findings may lead to targeted clinical treatments to prevent RV dysfunction and failure in PAH.